(untitled) (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: In Indonesia, such as on Barrang Lompo Island, much domestic waste is dumped directly into the environment, causing serious water pollution and threatening public health and the ecosystem. The use of a Moving Bed Biofilm Reactor (MBBR) biofilter combined with activated carbon can be an effective solution to this problem. AIM: This research aims to determine the effectiveness of the MBBR biofilter combined with activated carbon in reducing BOD, COD and TSS levels in domestic wastewater on Barrang Lompo Island. METHOD: The type of research used is quasi experimental designs by using a plan in the form of pre-test post-test. The population in this study is domestic liquid waste found on Barrang Lompo Island, and the sample is domestic liquid waste taken from the communal wastewater treatment plant on Barrang Lompo Island as a sample. pre-test and domestic liquid waste taken at the MBBR combined activated carbon biofilter outlet after processing as samples post-test. RESULTS: The research results showed that BOD levels had decreased by a percentage of 66.65% from the initial levels, COD levels had decreased by a percentage of 75.55% from the initial levels, TSS levels had decreased by a percentage of 45.3% from the initial levels. CONCLUSION: The MBBR biofilter combined with activated carbon is effective in reducing BOD and COD levels and quite effective in reducing TSS levels